Application Of Information Compression to Create New Hash Functional Algorithms of Rectangal Matrix Introduction (Texas Journal of Multidisciplinary Studies, 2022)
In article on the basis of results of research of properties of compression and single-sided rectangular matrixes the new algorithm of hashing function is developed